Floral structure and pollen load in relation to fruit development and physico-chemical characteristics of dragon fruit [Hylocereus polyrhizus (F.A.C Weber) Britton & Rose] at harvest - Cho, Joanna Lee Ying (2011)
In Malaysia, dragon fruits are graded and priced according to their fruit weight. As dragon fruit is a type of berry, its fruit weight depends on the number of developing seeds. In order to obtain better quality and yield in term of fruit weight, a study was conducted on the floral structure and pollen load on fruit development of red-fleshed dragon fruit (Hylocereus polyrhizus). The first objective was to determine the pollination events of H. polyrhizus. Light and scanning electron microscopy (SEM) were used to examine pollen and stigma morphology and pollen-stigma interaction of red-fleshed dragon fruit at 0, 1, 2, 3 and 4 day after pollination (DAP). Fluorescence microscopy was used to detect pollen tube growth stained with aniline blue in the style at 0, 2 and 4 DAP. The flowers of H. polyrhizus bloomed at night in an upright position with a spatial different between the anthers and the stigma suggesting cross-pollination. The pollen grains were categorized as large with polar axis (P) to equatorial diameter (E) ratio of 0.97, oblate spheroidal-shaped and trizonocolpate with the exine covered with echinates. The stigma had multiple lobes (n = 28 ± 3) and belonged to the dry type. The style is long (27 ± 2.54 cm) and solid with one hollow canal. Pollen grains germinated within 2 h after landing on the receptive stigma and pollen tubes grow within the transmitting tract located beneath the hollow canal of the style to the ovary. Starch granules within the style tissue depleted as DAP progressed. Findings indicated that a few pollen tubes had started to arrive in the ovary cavity after 2 DAP. Successful fertilization of male gametes (from pollen tube) with female gamete (ovule) led to fruit set. The second objective was to evaluate the changes in cellular structure using light microscopy and SEM during fruit development of H. polyrhizus at every 5 DAP. Starch pattern during fruit development was examined using iodine-potassium iodide (I2/KI). After successful fertilization, microscopic studies revealed that fruit development occurred in two distinct period of growth of cell division and cell expansion especially in the pulp region. Initially, parenchyma cells were small and rigid but loosen as DAP progressed. The early phase of cell division occurred in the first 20 DAP followed by cell enlargement thereafter. These cellular structure changes occurred concomitantly with the decrease of starch granules and colour change in the pulp. Starch granules accumulated within the pulp parenchyma cells and hydrolysed to sugar once the pulp turned red at 25 DAP as indicated by iodine stain clearing. For the third objective, effects of different pollen load size on H. polyrhizus fruits in term of fruit size and postharvest qualities were studied. Freshly dehisced pollen grains collected during anthesis were weighed at 0.001, 0.05, 0.10, 0.15 and 0.20 g (representing pollen load of 0.01, 0.5, 1.0, 1.5 and 2.0 x, respectively). The usual pollen load applied by the grower was used as control (C). Fruits were harvested at every 5 DAP until day 35. Results indicated that pollen load of 0.01 x produced the smallest fruit in term of fruit weight, length and diameter, followed by 0.5 x. Fruits of other treatments produced similar fruit size as control. There were no significant differences in peel and pulp colour, respiration rate and chemical characteristic among treatments except for soluble solids concentration (SSC). Smaller fruit tends to yield higher SSC. A positive correlation between seed number and fruit weight was determined (r = 0.931, P ≤ 0.001). In conclusion, flowers of H. polyrhizus are nocturnal bloomers with large pollen grains that are covered with echinates suggested zoophilous pollination. Fruits of H. polyrhizus are considered as fast crop as it took 30 days suggested by cellular structure and starch pattern change during fruit development. Findings indicated that fruit weight of H. polyrhizus could be manipulated by the amount of pollen grains as the pulp derived from the funiculli of developing seed.